A Porphodimethene Chemical Inhibitor of Uroporphyrinogen Decarboxylase - Yip, Kenneth W.; Zhang, Zhan; Sakemura-Nakatsugawa, Noriko; Huang, Jui-Wen; Vu, Nhu Mai; Chiang, Yi-Kun; Lin, Chih-Lung; Kwan, Jennifer Y. Y.; Yue, Shijun; Jitkova, Yulia; To, Terence; Zahedi, Payam; et al. (PLOS ONE, 2014)
Uroporphyrinogen decarboxylase (UROD) catalyzes the conversion of uroporphyrinogen to coproporphyrinogen during heme biosynthesis. This enzyme was recently identified as a potential anticancer target; its inhibition leads to an increase in reactive oxygen species, likely mediated by the Fenton reaction, thereby decreasing cancer cell viability and working in cooperation with radiation and/or cisplatin. Because there is no known chemical UROD inhibitor suitable for use in translational studies, we aimed to design, synthesize, and characterize such a compound. Initial in silico-based design and docking analyses identified a potential porphyrin analogue that was subsequently synthesized. This species, a porphodimethene (named PI-16), was found to inhibit UROD in an enzymatic assay (IC50 = 9.9 µM), but did not affect porphobilinogen deaminase (at 62.5 µM), thereby exhibiting specificity. In cellular assays, PI-16 reduced the viability of FaDu and ME-180 cancer cells with half maximal effective concentrations of 22.7 µM and 26.9 µM, respectively, and only minimally affected normal oral epithelial (NOE) cells. PI-16 also combined effectively with radiation and cisplatin, with potent synergy being observed in the case of cisplatin in FaDu cells (Chou-Talalay combination index <1). This work presents the first known synthetic UROD inhibitor, and sets the foundation for the design, synthesis, and characterization of higher affinity and more effective UROD inhibitors.